OC-074 Novel Point of Care Test for Detection of Human Phospholipase A2 to Predict Acute Pancreatitis Post Endoscopic Retrograde Cholangiopancreatography (ERCP) and Aid Same Day Discharge. (17th August 2016) - Phillips, N; Tyreman, M; Bentham, A; Bansi, D; Vlavianos, P; Westaby, D; Wadsworth, CA; Khan, SA
Abstract : Introduction: ERCP is a therapeutic procedure which carries a 5% risk of pancreatitis. Most patients who have undergone ERCP are admitted overnight for observation as it can take up to 12 hours for post-ERCP pancreatitis to manifest. Phospholipase A2 Group IB (PLA2GIB) is a sensitive marker of pancreatitis. A rapid, quantitative, point-of-care (POC) test for PLA2GIB has been developed. 1 We aimed to apply this test in a clinical setting, and determine its ability to detect clinically significant episodes of post-ERCP pancreatitis. Methods: Ethical approval for the study and informed patient consent were obtained. Patients undergoing ERCP were randomly selected within a tertiary referral HPB centre. Blood amylase levels were obtained before and 3 hrs after ERCP. At the same times, 20µL of blood was taken, added to a running buffer and applied to the POC kit. Movement of the diluent was observed along the lateral flow strip. The lateral flow strip was then read by a micro device, calculating the PLA2GIB concentration from a standard curve. Cases of post ERCP pancreatitis were idenitified on the basis of characteristic pain, examination findings and elevation in serum amylase. Results: 46 patients undergoing ERCP were recruited (26 M). Indication for ERCP included biliary stones (21), biliary strictures (12), biliary stent removal (6), pancreatic duct intervention (2) and other (5). The median pre-ERCP amylase level was 52 IU/L (range 19–316). The median post ERCP amylase was 78 IU/L (32–1720). Median pre-ERCP PLA2GIB concentration was 4 ng/mL (0.5–45). Median post-ERCP PLA2GIB was 6 ng/mL (0.6–418). There was a median 0.3 fold (-0.7-29) increase in PLA2GIB concentration after ERCP. 3 patients developed post-ERCP pancreatitis. These patients all had corresponding elevations in PLA2GIB above 70 ng/mL. A further 3 patients had elevation of amylase >3 x the upper limit of normal but without clinical symptoms of pancreatitis and with a PLA2GIB level <70 ng/mL. With a cut off level of 70 ng/mL, PLA2GIB had a sensitivity of 100% and specificity of 98%. The PPV was 75% and NPV 100%. Conclusion: This is the first clinical trial of a POC test for PLA2GIB activity. The test appears to be highly sensitive for post-ERCP pancreatitis. In our cohort of 46 patients undergoing ERCP, a negative test at 3 hours would have reliably excluded all cases of post-ERCP pancreatitis. This low cost, easy to use POC test could be used to support same day discharge of patients undergoing ERCP. Reference: 1 Chapman R, et al . Multivalent nanoparticle networks enable point-of-care detection of human phospholipase-A2 in serum. ACS Nano 2015;2565–2573. Disclosure of Interest: None Declared